Seismic Stratigraphy Interpretation and Petroleum Exploration at the Scarab field, Offshore, Nile Delta, Egypt - Mohamed , Maha Mahmoud Reda; Edress, Nader Ahmed Ahmed (IJRDO-Journal of Applied Science, 2021)
The Scarab field, situated in the Nile Delta concession of western Delta, has estimated that reservations of high-quality gas are greater than four trillion cubic feet. 2D Seismic dataset supported by composite logs enables the interpreter to generate a detailed view of the output results. Detection of the reservoir zone can be enhanced by analyzing wells log data based on Gamma-ray, Resistivity, and Vp sonic logs respectively. Composite logs of Scarab-Da, Scarab-Db, and Scarab-Dc wells indicate the lateral and vertical variation of the gas reservoir in El Wastani Formation. However, for enhancement of the detection of the hydrocarbon reservoirs, it is important to carefully analyze the well log dataset of the three wells as well as the available 2D seismic dataset. Based on the lithofacies distribution of the studied formation. The effective porosity and the hydrocarbon saturation increase in El Wastani Formation. In all wells, the average shale content is 0.35 %, the effective porosity is 0.20%, the water saturation is 0.25%, and the net pay range is 25 to 50 m. It is obvious that the facies effect is the main factor that is controlling the distribution of the petrophysical properties, within all wells.